Dependence risk analysis in energy, agricultural and precious metals commodities: A pair vine copula approach - Satish Kumar; Aviral Kumar Tiwari; Ibrahim Dolapo Raheem; Qiang Ji (African Governance and Development Institute (AGDI), 2019)
We apply pair vine copulas, specifically the C-vine and R-vine copulas, to examine the conditional multivariate dependence pattern/structure and R-vine copula-based value-at-risk (VaR) to assess financial portfolio risk. We examine the co-dependencies of 13 major commodity markets (which include three energy commodities, six agricultural commodities and four precious metals prices) from 2 January 2003 to 19 December 2016. Dividing our sample into three sub-periods, namely pre-GFC, GFC and post-GFC, we find that the dependencies among commodities undergo changes in a complex manner, changing in different financial conditions, and that the Student-t copula appears on the maximum number of occasions, especially during the GFC period, signifying the existence of fatter tails in the distributions of returns. We further show that the co-dependencies computed using R-vine copulas are best suited to compute the portfolio VaR during the considered time period.
Keywords: 330; R-vine; VaR; Dependence structure; Tree structure; Commodity markets